Pregnancy Outcome between Booked and Unbooked Cases in A Tertiary Level Hospital (Journal of Shaheed Suhrawardy Medical College, 2018)
To achieve the Sustainable Development Goals (SDG’2030) with regards to maternal health, there is need for research on the local causes and factors influencing adverse maternal & foetal outcomes in health institutions. Antenatal care throughout the pregnancy can ensure better feto-maternal outcome. It also contributed to reduction of maternal and infant mortality. This study was an attempt to enable health care providers to know where to focus to overcome adverse maternal outcome.Objectives: To find out the difference in maternal and perinatal outcome and socio-demographic characteristics in booked and unbooked cases. Design: A Cross-sectional observational study.Place of study :Department of Obststrics and Gynaeology , Shaheed Suhrawardy Medical College Hospital.Study period: April’2015 to july’2015. Study population- All patients admitted for delivery and puerperium during study period.Results: Unbooked mothers constituted 39.1% of the 218 deliveries in the studied period. There was no mean age difference between booked mothers and unbooked mothers (26.05±5.5 and 25.44±5.4; P=0.667) .But unbooked cases had a lower educational status (P